Rupture of a Coronary Artery Aneurysm and Fistula to the Pulmonary Artery. (September 2019) - Yeung, Darwin F.; Kiamanesh, Omid; Girgis, Hany; Hong, Jonathan; Turaga, Mansi; Gin, Kenneth; Wong, Graham C.; Janusz, Michael; Tsang, Michael Y.C.; Tsang, Teresa S.M.; Nair, Parvathy; Jue, John
Abstract : Supplemental Digital Content is available in the text.